1995
DOI: 10.1071/ea9950171
|View full text |Cite
|
Sign up to set email alerts
|

Lucerne reduces soil moisture and increases livestock production in an area of high groundwater recharge potential

Abstract: A grazing experiment was conducted on an area with high groundwater recharge potential in northeastern Victoria from 1988 to 1992. Merino wether weaners were grazed on either lucerne (Medicago sativa) or a pasture consisting of annual species (Trifolium spp., Lolium rigidum, Vulpia bromoides, Hordeum leporinum) at 5.0, 8.75, or 12.5 wethers/ha. Lucerne pastures were rotationally grazed and annual pastures were set-stocked. Measurements included herbage mass, lucerne plant density, sheep liveweight, wool produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Dryland salinity, resulting from the continual use for cropping of areas previously covered by trees, is an increasing problem worldwide with, for example, a large proportion of south‐western Australia (4.4 million ha) at high risk from shallow watertables (National Land and Water Resources Audit, ). The high water‐use of lucerne and its ability to help control this problem has therefore attracted much attention (Crawford & Macfarlane, ; Ridley et al , ; Humphries & Auricht, ). The lucerne industry generates US$7 billion annually and covers 32 million ha, one‐third of which is in the U.S.A. (Michaud et al , ; Şakiroğlu & Brummer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Dryland salinity, resulting from the continual use for cropping of areas previously covered by trees, is an increasing problem worldwide with, for example, a large proportion of south‐western Australia (4.4 million ha) at high risk from shallow watertables (National Land and Water Resources Audit, ). The high water‐use of lucerne and its ability to help control this problem has therefore attracted much attention (Crawford & Macfarlane, ; Ridley et al , ; Humphries & Auricht, ). The lucerne industry generates US$7 billion annually and covers 32 million ha, one‐third of which is in the U.S.A. (Michaud et al , ; Şakiroğlu & Brummer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Soil water storage was signifi cantly affected by the succession stage (p<0.05). During the fi rst 7 years, alfalfa was the predominant species, and its high evapotranspiration rate and deep root system resulted in higher water consumption, reported to be at least 50 mm over that of other cultivated species (Crawford & Macfarlane, 1995;Dunin et al, 2001;Li & Huang, 2008). Thus, soil water storage was at its lowest for the fi rst two succession stages throughout the growing season.…”
Section: Yearsmentioning
confidence: 99%
“…Alfalfa is a summer-active species with deep roots, which enable it to extract water deep within the soil profi le and to maintain high transpiration rates. High water consumption by alfalfa frequently exceeds local precipitation during the growing season (Crawford & Macfarlane, 1995;Li & Huang, 2008). Li (1983) observed that relatively dry soil layers had formed at 2 to 10 m depth after six years of alfalfa growth, causing water stress to the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Low precipitation and high potential evapotranspiration are considered as the main limitations to the establishment and growth of seeded species in semi-arid regions (Munson and Lauenroth, 2011). Legume species such as Medicago have high water consumption and evapotranspiration rates (Crawford and Macfarlane, 1995;Scott and Sudemyer, 1993), and their growth is influenced by precipitation (Jia et al, 2009;Li and Huang, 2008). Thus, inter-annual variability in rainfall may influence the interaction of introduced legume species and naturally occurring late-successional species, and thus vegetation development during the early stages of secondary succession.…”
Section: Discussionmentioning
confidence: 98%